REPRESENTASI EMANSIPASI WANITA DALAM BUDAYA JAWA PADA FILM KARTINI (2017) - Ayudia Putri, Rakhma; Rahardjo, Turnomo; Lukmantoro, Triyono (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2024)
The dissemination of values brought by films as mass media can influence society in constructing ideologies. In media ecology theory, media are considered more than just channels for message transmission; the inherent nature of the medium can be key to a social impact. This includes how various gender aspects regarding the portrayal of women's roles in films can affect societal perspectives and ideologies.